2018
DOI: 10.1093/cjres/rsy013
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of entrepreneurial ecosystems and the critical role of migrants. A Phase-Model based on a Study of IT startups in the Greater Tel Aviv Area

Abstract: Unlike existing studies on entrepreneurial ecosystems that focus on the internal dynamics of such systems, this article argues that entrepreneurial ecosystems are linked to one another through economically specialised migrants that trigger their emergence and positively affect their future development. To illustrate the relation between migration and the dynamics of entrepreneurial ecosystems, a model is presented that distinguishes three different phases: (i) the remigration of highly skilled migrants, (ii) ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…The papers included in this review highlight how entrepreneurs, other ecosystem actors, and, by extension, ideas, practices, and norms move between ecosystems and across spatial, cultural, and language barriers (Fraiberg, 2017;Schäfer & Henn, 2018). The result is a bi-directional learning process for both migrant entrepreneurs and ecosystems (Steinz et al, 2016).…”
Section: Inter-ecosystem Linksmentioning
confidence: 99%
“…The papers included in this review highlight how entrepreneurs, other ecosystem actors, and, by extension, ideas, practices, and norms move between ecosystems and across spatial, cultural, and language barriers (Fraiberg, 2017;Schäfer & Henn, 2018). The result is a bi-directional learning process for both migrant entrepreneurs and ecosystems (Steinz et al, 2016).…”
Section: Inter-ecosystem Linksmentioning
confidence: 99%
“…The world has become increasingly transnational, and the migration phenomenon has become increasingly complex. There are different types of entrepreneurs with migration backgrounds, such as transnational entrepreneurs (Drori et al 2009;Schäfer and Henn 2018) and second-generation ethnic entrepreneurs (Dang and Harima 2020;Rusinovic 2008). The idea of mixed embeddedness, which mainly considers the mainstream and ethnic markets in host countries, offers limited explanations when migrants are embedded in more contexts than these two or in transnational contexts.…”
Section: Limitations and Research Outlookmentioning
confidence: 99%
“…Only nine of these are empirical and even these limited few have methodological dissonance having been widely reproached for a failure to extend beyond a static framework and attendant inability to capture evolutionary processes over time (Acs et al, 2017;Adams, 2020;Alvedalen & Boschma, 2017;Cavallo et al, 2019;Stam, 2015). In Table 3, we identify merely 10 longitudinal studies in our population and only four of these (Auerswald & Dani, 2017;Ryan et al, 2020;Schäfer & Henn, 2018;Thompson et al, 2018) are also to be observed in the list of EE evolution studies. Previous EE review articles also point to the drawback of static studies and lack of dynamism and longitudinal methods and approaches, but tangentially and without much guidance for rectification and theoretical advancement (Alvedalen & Boschma, 2017;Brown & Mason, 2017;Malecki, 2018).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%